Castleman Lymphadenopathy Presenting as Axillary Mass in a 69-Year-Old Male: A Case Report with Review of Literature - Kour, Prableen; Sharma, Anuja; Malhotra, Aneeta Singh; Raina, Bawana (Annals of Pathology and Laboratory Medicine, 2025)
Castleman disease (CD), first described by Benjamin Castleman, is a rare and heterogeneous disorder of unknown aetiology, characterised by massive lymphadenopathy and a range of systemic inflammatory symptoms. It shows no specific predilection for age, gender, or ethnicity and exhibits distinctive histomorphological features. Depending on the extent of involvement, CD can be classified as either unicentric or multicentric, each with distinct clinical presentations. Unicentric CD (UCD) presents as localised lymphadenopathy, usually without any other symptoms. In contrast, multicentric CD (MCD) is a progressive, systemic inflammatory condition involving multiple lymph node stations and organ systems. Histologically, two main morphological variants are recognised: the hyaline vascular (HV) type and the plasma cell (PC) type. We herein report a case of a 69-year-old male who presented to our hospital with a painless, gradually enlarging axillary swelling, which, on imaging, appeared as a conglomerate of enlarged lymph nodes. Radiological findings were non-specific, and aspiration cytology was suggestive of Rosai-Dorfman disease. The diagnosis of CD is generally delayed and fraught with challenges since it is rare and can mimic a broad array of entities, encompassing lymphomas, granulomatous inflammation, autoimmune disorders, among others. Histopathological analysis of the excised lymph node is considered the best modality for diagnosing and distinguishing the various subtypes of CD.